Pemikiran Fikih Perempuan dalam Kitab Parukunan Banjar - Yamani, Antung; Ariyadi, Ariyadi; Muhammad Wahdini (Al-Qalam: Jurnal Kajian Islam dan Pendidikan, 2023)
This paper discusses the thoughts of Banjar women scholars as outlined in the great Parkununan book. The book which was originally given the name "Parukunan Besar" is thought to have been written in the 1820s. Parukunan is a basic book which contains the basic pillars of purification or thhaharoh such as ablution, bathing, tayammum, prayer, attribute 20 and other important prayers. This Parkunan book was written by a Banjar woman scholar named Fatimah bint Syekh Abdul Wahab Bugis. The urgency of this research is shown that the role of female clerics at that time was evidently present in the absence of freedom of expression for women, even the Parukunan book by Fatimah had to attribute the author's name to her uncle, Sheikh Jamaludin. This research is classified as library research by studying literature or classic manuscripts. In this book, various chapters are explained, namely matters of Aqidah, Worship, and some of the interesting mu'amalahs, there are special chapters that discuss women's issues, namely menstruation, childbirth, wiladah and istihadhah